Multiscale Analysis of the Strength Deterioration of Loess under the Action of Drying and Wetting Cycles - Yang Bai; Wanjun Ye; Yuntao Wu; Yiqian Chen (Advances in Materials Science and Engineering)
To study the strength degradation mechanism of compacted loess during dry-wet cycles, 0–5 dry-wet cycles tests and many triaxial compression tests were carried out on loess with an optimal moisture content. During the dry-wet cycles, the loess samples were analyzed by nuclear magnetic resonance and scanning electron microscopy. Studies have shown that at the macro level, with increasing numbers of wet and dry cycles and increasing cycle amplitude, the cohesive force and internal friction angle of the loess decrease, and the shear strength of the loess deteriorates significantly. At the micro level, with the number of wet and dry cycles increasing, the connection between particles changes from surface-to-surface contacts to point-to-point or point-to-surface contacts. The edges and corners of the particles decrease, the roundness increases, the large pores gradually decrease, the small pores gradually increase, and the fractal dimension gradually increases. In terms of microscopic view, the NMR test shows that with increasing numbers of dry-wet cycles, the T2 peak curve increases, the curve width increases slightly, the peak area gradually increases, and the porosity increases. From the macroscopic, mesoscopic, and microscopic multiscale analysis, the structure of loess is degraded under the action of dry and wet cycles; the strength of the loess is degraded significantly after 0 to 3 cycles and then gradually stabilizes. These research results can provide a certain reference value for the management of loess collapse geological disasters in semiarid climates.